Engineering the Band Alignment in QD Heterojunction Films via Ligand Exchange - Grimaldi, Gianluca; Van Den Brom, Mark J.; Du Fosse, Indy; Crisp, Ryan; Kirkwood, Nicholas; Gudjonsdottir, Solrun; Geuchies, Jaco J.; Kinge, Sachin; Siebbeles, Laurens D. A.; Houtepen, Arjan J. (Journal of Physical Chemistry C, 2019)
Colloidal quantum dots (QDs) allow great flexibility in the design of optoelectronic devices, thanks to their size-dependent optical and electronic properties and the possibility to fabricate thin films with solution-based processing. In particular, in QD-based heterojunctions, the band gap of both components can be controlled by varying the size of the QDs. However, control over the band alignment between the two materials is required to tune the dynamics of carrier transfer across a heterostructure. We demonstrate that ligand exchange strategies can be used to control the band alignment of PbSe and CdSe QDs in a mixed QD solid, shifting it from a type-I to a type-II alignment. The change in alignment is observed in both spectroelectrochemical and transient absorption measurements, leading to a change in the energy of the conduction band edges in the two materials and in the direction of electron transfer upon photoexcitation. Our work demonstrates the possibility to tune the band offset of QD heterostructures via control of the chemical species passivating the QD surface, allowing full control over the energetics of the heterostructure without requiring changes in the QD composition.